Indices of bio-agroeconomic efficiency in intercropping systems of cucumber and lettuce in greenhouse - Filho, Arthur Bernardes Cecílio [UNESP]; Neto, Francisco Bezerra; Rezende, Bráulio Luciano Alves; Barros Júnior, Aurélio Paes; de Lima, Jailma Suerda Silva (My University, 2015)
The adoption of alternative practices and the conservation of agricultural production are becoming a component of competitiveness in the market, because consumers are increasingly concerned about the ecological and social aspects of agricultural production. The intercropping of vegetables is a system of production that can contribute to a solution. Intercropping cucumber and lettuce has not yet been studied, but knowledge of the indices of competition and the agroeconomics of these vegetables can aid the management of intercropping systems. The objective of this study was to evaluate, by means of biological and agroeconomic indices, the competition between species and the profitability of intercropping cucumber and lettuce, as a function of population densities of cucumber plants, cultivars of lettuce, and times of lettuce transplantation after cucumber transplantation. Four experiments originated from two lettuce cultivars (crisp, cv. Verônica, and Iceberg, cv. Lucy Brown) intercropped with cucumber (cv. Hokushin) planted in one and two lines in the densities of 11 100 and 22 200 pl ha-1, respectively, were conducted in two greenhouses, in a randomized complete block design, to evaluate four times of lettuce transplantation (0, 10, 20 and 30 days after the cucumber transplantation). In each block were planted four plots with lettuce in sole crop in these same transplantation times, besides a plot with cucumber in monocrop, in order to determine the indices of bio-agroeconomic efficiency of the intercropping systems. A combined analysis of variance over experiments was performed for all evaluated indices to identify any significant interaction between population densities of cucumber and lettuce cultivars, or between population densities of cucumber and times of lettuce transplantation after cucumber transplantation, or between lettuce cultivars and times of lettuce transplantation after cucumber transplantation, or among population densities of cucumber, lettuce cultivars and times of lettuce transplantation after cucumber transplantation. The intercropping systems of lettuce and cucumber produced bio-agroeconomic advantages over monocultures. The intercropping system with the highest bio-agroeconomic superiority obtained was when the lettuce 'Verônica' was intercropped with cucumber at 11 100 pl ha-1, with both species transplanted on the same day.
Keywords: Cucumis sativus; Efficiency indicators; Lactuca sativa; Protected environment